Role of Glutamatergic Excitotoxicity in Neuromyelitis Optica Spectrum Disorders - Silva, Ana Paula Bornes da; Souza, Débora Guerini; Souza, Diogo Onofre; Machado, Denise Cantarelli; Sato, Douglas Kazutoshi (Frontiers in Cellular Neuroscience, 2019)
Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory disorder mediated by immune-humoral responses directed against central nervous system (CNS) antigens. Most patients are positive for specific immunoglobulin G (IgG) auto-antibodies for aquaporin-4 (AQP4), a water channel present in astrocytes. Antigen-antibody binding promotes complement system cascade activation, immune system cell infiltration, IgG deposition, loss of AQP4 and excitatory amino acid transporter 2 (EAAT2) expression on the astrocytic plasma membrane, triggering necrotic destruction of spinal cord tissue and optic nerves. Astrocytes are very important cells in the CNS and, in addition to supporting other nerve cells, they also regulate cerebral homeostasis and control glutamatergic synapses by modulating neurotransmission in the cleft through the high-affinity glutamate transporters present in their cell membrane. Specific IgG binding to AQP4 in astrocytes blocks protein functions and reduces EAAT2 activity. Once compromised, EAAT2 cannot take up free glutamate from the extracellular space, triggering excitotoxicity in the cells, which is characterized by overactivation of glutamate receptors in postsynaptic neurons. Therefore, the longitudinally extensive myelitis and optic neuritis lesions observed in patients with NMOSD may be the result of primary astrocytic damage triggered by IgG binding to AQP4, which can activate the immune-system cascade and, in addition, downregulate EAAT2. All these processes may explain the destructive lesions in NMOSD secondary to neuroinflammation and glutamatergic excitotoxicity. New or repurposed existing drugs capable of controlling glutamatergic excitotoxicity may provide new therapeutic options to reduce tissue damage and permanent disability after NMOSD attacks.